Usability Evaluation the Prague Geoportal : Comparison of Methods - Komárková, Jitka; Sedlák, Pavel; Struška, Stanislav; Dymáková, Andrea (IEEE (Institute of Electrical and Electronics Engineers), 2019)
Usability is an important quality characteristic of software products. It is focused directly on users, namely on the quality of user interface. There have been proposed many various usability evaluation and testing methods. The methods differ from many points of view, e.g. used tools, involved participants, obtained results, stage of the system development life cycle, etc. The paper describes a case study which uses combination of usability user testing, survey and heuristic evaluation to evaluate usability of the Prague Geoportal. Case study shows that very similar results are obtained by the methods. Average time necessary for usability evaluation and testing planning, testing itself and results assessment is different. Different is a level of detail of obtained results. Combinations of different methods is useful because it brings different points of view.
Hodnocení použitelnosti Geoportálu Prahy: porovnání metod
Keywords: Usability; user testing; heuristic evaluation; Web-based GIS; geoportal; Použitelnost; uživatelské testování; heuristické hodnocení; webový GIS; geoportál